Lifestyle and environmental risk factors associated with cancer: A case-control study in Bangladesh - Mohammad Lutfor Rahman; K. M. Tanvir; Farzana Rahman; Sreshtha Chowdhury; Shuvajit Saha; Md Abdullah Saeed Khan; Mohammad Azmain Iktidar; Mehedi Hasan; Samiha Nahar Tuli; Sharmin Akter; Tajrin Rahman; Mohammad Hayatun Nabi; et al. (PLoS ONE, 2026)
Cancer remains the second leading cause of death worldwide, with cases rising at an alarming rate. While the causes of cancer are complex and varied, certain risk factors - such as exposure to environmental pollutants and specific lifestyle choices - are modifiable and can be addressed. A case-control study was conducted in Bangladesh from 25 August 2023 to 18 April 2024 to examine the association between cancer risk and a range of lifestyle and environmental factors. The study specifically focused on six common cancer types: breast, hematological, oral, cervical, colorectal, and lung cancer. This study identified several lifestyle and environmental factors positively associated with cancer risk. Individuals using wood or kerosene for cooking had higher odds of cancer compared to those using supplied gas (AOR = 3.886). Consumption of overcooked or poorly cooked food was associated with an increased risk of cancer compared to the consumption of well-cooked food (AOR = 2.478). Oral hygiene also showed a relationship, with participants brushing their teeth only 2-3 times a week having a higher chance of cancer compared to those who brush regularly (AOR = 3.103). In addition, frequent exposure to mosquito repellent was positively associated with cancer risk (AOR = 1.569), and exposure to inorganic dust showed a similar association (AOR = 1.673). These findings highlight modifiable lifestyle and environmental factors that could inform future cancer prevention strategies in Bangladesh.